Manual Sobre Cuidados Com A Ferida Pós Pleurostomia Aberta - Santana, Alcione De Jesus Goncalves [UNIFESP] (2018)
Introduction: Caring for an open post-pleurostomy wound is a challenge, there are few studies which describe about the care with the post-pleurostomy wound that may help in the decision making and adequate orientations. The use of informative manuals is one of the strategies which can be utilized for the orientation and direction of the conduct of the nurses. Objective: Developing a manual about the care with the open post-pleurostomy wound for health professionals. Methods: Manual developing study. It wasapproved by CEP of the UNIFESP CAAE: 67970117.7.0000.5505. It has not been held the search of anteriority, and it has not been found a manual alike. For the content’s development, it has been consulted the bibliographic databases and Cochrane, Scielo, LILACS and PubMed, Google Scholar search websites. It has been selected articles in Portuguese, Spanish and English in the period of 2010 and 2017. The descriptors used in the search were: toracotomy, toracostomy, thoracic cavity, pleura, pleural cavity, wounds and lesions. In the sequence, it has been elaborated the text, the illustrations and the text formatting. After developing the manual, it was evaluated by experts. For the validation of the manual was used the CVI (Content Validation Index). Results: The manual that was developed has thirty-six pages, seven chapters with the following themes: Introduction, Care with the open post-pleurostomy, Wound/Debridement Cleaning, Wound Dressings, Care Records, Final Considerations, Bibliography. Conclusion: It has been developed a care with an open post-pleurostomy wound manual and confirmed its validation for the usage of health professionals.